Damang's Existence as a Customary Justice of Peace in the Dayak Tribe Community in Palangkaraya - Arma Diansyah (Asian Journal of Social and Humanities, 2023)
Demang is a customary leader who serves as the chief of customary region (kedemangan). The research method used in this research is based on empirical legal research on primary and secondary data. The data was qualitatively processed and analyzed. The overall results of the analysis are descriptively presented, that is describing the problems fully combined with critical commentaries. The theory used in this thesis is the theory of the Legal System Theory by Lawrence M. Friedman and some teachings on traditional case handling by Moh. Koesnoe. Both these theories are used as a analysis knife to dissect and analyze the issues being studied. The discussion and the conclusion of this thesis, can be described as follows: (1).The existence of the position of Demang as a Peace Judge of indigenous communities judicially recognized in the legislation in force and still adhered to by the Dayak people in Palangkaraya, (2).In performing its functions, Demang as a Peace Judge of indigenous communities, always prioritizes the ways of peace settlement based on the principle of harmony, mutual grindstones, mutual love, mutual care, so as to solve the problem completely and the results can satisfy all parties, (3).In fact, the Dayak community legal culture in Palangkaraya strongly supports the effective execution of tasks of Demang as a Judge of Peace, from the cases that came to kedemangan, none of the cases has been brought to the level above kedemangan or appeal to local courts, (4).In current conditions, the role of Demang as a Judge of Peace needs to be enhanced in order to remain effective and not lose its function. Steps of empowerment can be done internally and externally, internally more on improving human resources and ways to resolve cases of indigenous peoples. Then externally rather the provision of facilities and infrastructure supporting the Demang duties performance as a Indigenous Judge of Peace